Multi-component composite industrial solid waste concrete and preparation method thereof
Through the use and optimized proportion design of diversified composite industrial solid waste materials, the problems of unstable strength and single performance of industrial solid waste concrete are solved, and the preparation of high-performance concrete is realized, meeting different engineering needs and meeting the requirements of sustainable development.
Patent Information
- Application Number
- CN202411956369.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-28
- Publication Date
- 2025-04-11
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing industrial solid waste concrete has problems such as unstable strength and single performance, which is difficult to meet the needs of different engineering fields.
High-performance concrete is prepared by using diverse composite industrial solid waste materials, including fly ash, slag, limestone powder, machined sand and tailings sand, combined with the ratio design of different strength grades. The method includes pretreatment and optimized preparation processes to ensure the stability and reliability of concrete properties.
It realizes the adjustability of concrete strength grades, meets different engineering needs, reduces the exploitation of natural resources and environmental pollution, and meets the requirements of sustainable development.
Smart Images

Figure CN119797837A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of building materials, and in particular relates to a multi-component composite industrial solid waste concrete and a preparation method thereof. Background Art
[0002] With the acceleration of industrialization, the amount of industrial solid waste generated is increasing, such as fly ash, slag, limestone powder, machine-made sand, tailings sand, etc. The large accumulation of these industrial solid wastes not only occupies land resources, but also causes serious pollution to the environment. At the same time, the traditional concrete preparation process requires a large amount of natural resources, such as river sand, natural stone, etc. The mining of these resources has aggravated the damage to the ecological environment. Therefore, it is of great significance to develop a technology that can efficiently utilize industrial solid waste to prepare high-performance concrete.
[0003] In order to solve the above problems, researchers began to explore the method of using industrial solid waste to prepare concrete. However, the current industrial solid waste concrete has problems such as unstable strength and single performance, which makes it difficult to meet the needs of different engineering fields. Summary of the invention
[0004] In order to solve the problems of unstable strength and single performance of industrial solid waste concrete in the above-mentioned prior art, and the difficulty in meeting the needs of different engineering fields, the present invention provides a multi-component composite industrial solid waste concrete and a preparation method.
[0005] The present invention is implemented by the following technical scheme: comprising several strength grades, the strength grades are 20MPa≤strength grade<30MPa, 30MPa≤strength grade<50MPa and 50MPa≤strength grade<100MPa, and the concrete composition ratios corresponding to the strength grades are as follows:
[0006] 20MPa≤Strength grade<30MPa: cement 5.8%-11.5%, fly ash 2.0%-8.0%, slag 1.5%-8.0%, limestone powder 0%-10.0%, machine-made sand 18.0%-25.0%, tailings sand 10.0%-23.0%, water 7.0%-8.5%, admixture 0.29%-0.42%;
[0007] 30MPa≤Strength grade<50MPa: cement 7.0%-17.0%, fly ash 2.0%-7.0%, slag 1.5%-7.0%, limestone powder 0%-10.0%, machine-made sand 9.5%-20.0%, tailings sand 8.5%-22.5%, water 6.5%-7.5%, admixture 0.27%-0.36%;
[0008] 50MPa≤Strength grade<100MPa: cement 8.0%-18.0%, fly ash 1.5%-6.0%, slag 1.5%-6.0%, limestone powder 0%-8.0%, silica fume 0%-2.5%, natural sand 0%-32.5%, machine-made sand 16.0%-22.5%, tailings sand 7.5-9.5%, water 5.0-7.0%, admixture 0.4-0.5%;
[0009] Among them, the proportion of each component is the proportion of the total weight of concrete, and the remaining components are crushed stone or natural sand.
[0010] As a further preference, the cement is silicate cement P.O42.5 when the concrete strength grade is between 20MPa and 50MPa, and is silicate cement P.O52.5 when the concrete strength grade is between 50MPa and 100MPa.
[0011] As a further preference, the fly ash is primary fly ash with a loss on ignition ≤5% and a D50 particle size of 6.017 μm, wherein the content of fly ash particles smaller than 3 μm is ≤30%, and the content of fly ash particles of 3 μm-32 μm is ≥66%.
[0012] As a further preference, the slag is of S95 grade, with a mass fraction of 1.46, an activity coefficient of 0.31, an alkalinity coefficient of 0.91, a 28-day activity coefficient ≥95%, a fluidity ratio ≥95%, a loss on ignition ≤3.0%, and a glass content ≥85%.
[0013] As a further preference, the limestone powder has a D50 particle size of 2.859 μm, wherein the content of limestone powder particles smaller than 3 μm is 52%, and the content of limestone powder particles of 3 μm-32 μm is 48%.
[0014] As a further preference, the SiO2 content of the silica ash is ≥96%, the loss on ignition is ≤2.5%, and the activity index is ≥105%.
[0015] As a further preference, the tailings sand and machine-made sand are mixed into fine aggregate in a ratio of 25%-45% tailings sand and 55%-75% machine-made sand, and the fineness modulus of the fine aggregate is 2.6.
[0016] As a further preferred embodiment, the apparent density of the machine-made sand is 2600-2800 kg / m 3 , bulk density 1750-1900kg / m 3 , crushing value 25%; tailings sand apparent density 2600-2800kg / m 3 , bulk density 1500-1700kg / m 3 .
[0017] As a further preference, the admixture is a polycarboxylic acid high-efficiency water reducing agent, and the water reducing rate is ≥25%.
[0018] The present invention also provides a method for preparing the multi-component composite industrial solid waste concrete according to the present invention, comprising the following steps:
[0019] S1. Determine the strength grade of concrete according to usage requirements;
[0020] S2. Pre-treat fly ash, slag, limestone powder, machine-made sand and tailings sand;
[0021] S3, according to the concrete strength grade determined in step 1, weigh and measure the pre-treated fly ash, slag, limestone powder, machine-made sand and tailings sand with cement, water, admixtures, silica fume, natural sand and crushed stone;
[0022] S4, adding the fly ash, slag, limestone powder, machine-made sand, tailings sand, cement, silica fume, natural sand and gravel measured in step 3 into a mixer, and dry mixing for 5-10 minutes;
[0023] S5. Add half of the water and admixture measured in step 3 into the mixer and stir for 5-10 minutes until the concrete is loose.
[0024] S6. Add the remaining water and admixtures, stir mechanically until uniform, and carry out standard curing after casting.
[0025] Compared with the prior art, the present invention has the following beneficial effects:
[0026] 1. The present invention uses fly ash, slag, limestone powder, machine-made sand, tailings sand and other industrial solid waste materials for compounding, giving full play to the advantages of different solid waste materials, thereby improving the performance of concrete.
[0027] 2. The present invention realizes the adjustable concrete strength grade in a wide range through reasonable mix ratio design to meet different engineering requirements.
[0028] 3. The present invention utilizes a large amount of industrial solid waste materials, reduces the exploitation of natural resources and the pollution to the environment, and meets the requirements of sustainable development.
[0029] 4. The present invention ensures the stable and reliable performance of multi-component composite industrial solid waste concrete by pretreatment and optimization of the preparation process. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 It is the overall flow chart of the preparation method of the present invention. DETAILED DESCRIPTION
[0031] Advantages and features of the present invention will be illustrated and explained by the following non-limiting description of preferred embodiments thereof, which are given by way of example only with reference to the accompanying drawings.
[0032] The present invention provides a multi-component composite industrial solid waste concrete, which can be divided into several strength grades, namely: 20MPa≤strength grade<30MPa, 30MPa≤strength grade<50MPa and 50MPa≤strength grade<100MPa. The concrete proportions of different strength grades are as follows, where the proportion of the components is the proportion of the total weight of the concrete, and the remaining components of the concrete are crushed stone or natural sand:
[0033] 20MPa≤Strength grade<30MPa: cement 5.8%-11.5%, fly ash 2.0%-8.0%, slag 1.5%-8.0%, limestone powder 0%-10.0%, machine-made sand 18.0%-25.0%, tailings sand 10.0%-23.0%, water 7.0%-8.5%, admixture 0.29%-0.42%;
[0034] 30MPa≤Strength grade<50MPa: cement 7.0%-17.0%, fly ash 2.0%-7.0%, slag 1.5%-7.0%, limestone powder 0%-10.0%, machine-made sand 9.5%-20.0%, tailings sand 8.5%-22.5%, water 6.5%-7.5%, admixture 0.27%-0.36%;
[0035] 50MPa≤Strength grade<100MPa: cement 8.0%-18.0%, fly ash 1.5%-6.0%, slag 1.5%-6.0%, limestone powder 0%-8.0%, silica fume 0%-2.5%, natural sand 0%-32.5%, machine-made sand 16.0%-22.5%, tailings sand 7.5-9.5%, water 5.0-7.0%, admixture 0.4-0.5%.
[0036] Among them, the requirements for the selected raw materials are as follows:
[0037] Cement: Choose ordinary Portland cement or other suitable cement varieties that meet national standards. When making concrete with a compressive strength of 20MPa to 50MPa, choose Portland cement P.O42.5; when making concrete with a compressive strength of 50MPa to 100MPa, choose Portland cement P.O52.5.
[0038] Industrial solid waste materials:
[0039] Fly ash: Use first-grade fly ash with a loss on ignition of ≤5%. The D50 particle size of fly ash particles is 6.017μm, of which the content of fly ash particles smaller than 3μm is ≤30%, and the content of fly ash particles between 3μm and 32μm is ≥66%.
[0040] Slag: S95 grade, mass fraction 1.46, activity coefficient 0.31, alkalinity coefficient 0.91, 28-day activity coefficient ≥ 95%, fluidity ratio ≥ 95%, loss on ignition ≤ 3.0%, glass content ≥ 85%.
[0041] Limestone powder: Choose limestone powder with moderate fineness and stable chemical composition. The D50 particle size is 2.859μm, of which the content of limestone powder particles smaller than 3μm is 52%, and the content of limestone powder particles between 3μm and 32μm is 48%.
[0042] Silica fume: SiO2 content ≥96%, loss on ignition ≤2.5%, activity index ≥105%.
[0043] Fine aggregate: tailings sand 25%-45%, machine-made sand 55%-75%, fineness modulus 2.6. Apparent density of machine-made sand 2600-2800kg / m 3 , bulk density 1750-1900kg / m 3 , crushing value 25%; tailings sand apparent density 2600-2800kg / m 3 , bulk density 1500-1700kg / m 3 .
[0044] Coarse aggregate: crushed stone with particle size of 5-20mm and 5-31.5mm in continuous grading.
[0045] Admixture: Mainly water reducer, preferably polycarboxylic acid high-efficiency water reducer, with a water reduction rate of ≥25%.
[0046] like Figure 1 As shown, the present invention also provides a method for preparing multi-component composite industrial solid waste concrete, comprising the following steps:
[0047] Step 1: Determine the strength grade of concrete according to usage requirements.
[0048] Step 2: pre-treat fly ash, slag, limestone powder, machine-made sand and tailings sand.
[0049] The pretreatment method includes: drying and grinding fly ash to improve its activity and fineness; grinding slag to increase its specific surface area and activity index; screening and removing impurities from limestone powder to ensure its fineness and chemical composition stability; washing and screening machine-made sand and tailings sand to reduce mud content and harmful substance content.
[0050] Step 3: According to the concrete strength grade determined in step 1, the pre-treated fly ash, slag, limestone powder, machine-made sand and tailings sand are weighed and measured with cement, water, admixtures, silica fume, natural sand and crushed stone.
[0051] Step 4: Add the fly ash, slag, limestone powder, machine-made sand, tailings sand, cement, silica fume, natural sand and gravel measured in step 3 into a mixer and dry mix for 5-10 minutes to fully mix the dry materials.
[0052] Step 5: Add half of the water and admixture measured in step 3 into the mixer and stir for 5-10 minutes until the concrete is loose and there is not too much dry powder.
[0053] Step 6: Add the remaining water and admixtures, stir mechanically until uniform, and carry out standard curing after casting.
[0054] Example 1
[0055] The weights of cement, fly ash, slag, machine-made sand, tailings sand, crushed stone, water and admixtures in multi-component composite industrial solid waste concrete are 175, 75, 50, 583.1, 250, 1080, 180 and 7.2 respectively, in grams, and their proportions to the total weight of concrete are 7.3%, 3.1%, 2.1%, 24.3%, 10.4%, 45.0%, 7.5% and 0.3% respectively.
[0056] Cement: Use silicate cement P.O42.5;
[0057] Fly ash: First-grade fly ash, loss on ignition 5%, D50 particle size 6.017μm, fly ash particles smaller than 3μm content 28%, fly ash particles 3μm-32μm content 70%.
[0058] Slag: S95 grade, mass fraction 1.46, activity coefficient 0.31, alkalinity coefficient 0.91, 28-day activity coefficient 95%, fluidity ratio 95%, loss on ignition 2.5%, glass content 87%.
[0059] Fine aggregate: 30% tailings sand, 70% machine-made sand, fineness modulus 2.6. Apparent density of machine-made sand 2600kg / m 3 , bulk density 1800kg / m 3 , crushing value 25%; tailings sand apparent density 2600kg / m 3 , bulk density 1600kg / m 3 .
[0060] Coarse aggregate: crushed stone with particle size of 5-20mm and 5-31.5mm in continuous grading.
[0061] Admixture: Polycarboxylic acid high-efficiency water reducing agent, water reducing rate 27%.
[0062] Preparation method of multi-component composite industrial solid waste concrete:
[0063] Determine the strength grade as: 20MPa≤strength grade<30MPa; pretreat fly ash, slag, machine-made sand and tailings sand; weigh and measure the pretreated fly ash, slag, machine-made sand and tailings sand with cement, water, admixtures and gravel; add the measured fly ash, slag, machine-made sand, tailings sand, cement and gravel into a mixer and dry mix for 5 minutes; add half of the measured water and admixture into the mixer and stir for 5 minutes; add the remaining water and admixture and mechanically stir until uniform.
[0064] The mixed concrete was discharged, and the concrete performance test was carried out according to the "Standard for Test Methods for Performance of Ordinary Concrete Mixtures" (GB / T50080-2016). According to the "Standard for Test Methods for Physical and Mechanical Properties of Concrete" (GB / T50081-2019), test specimens for concrete compressive strength, flexural strength, splitting strength and other indicators were made. Among them, the cube compressive strength test and splitting tensile strength test used 150mm×150mm×150mm specimens, and the axial compressive strength test and elastic modulus test used 150mm×150mm×300mm specimens. The specimens were all maintained in standard manner, and the curing ages were 7d, 14d, 28d, 60d, and 90d, respectively, and the tests were carried out at the corresponding ages. One group of specimens was cast at each age, with 3 test blocks in each group.
[0065] The test shows that the compressive strength of the concrete sample in this embodiment after 60 days of curing is 26.2 MPa.
[0066] Example 2
[0067] The weights of cement, fly ash, slag, machine-made sand, tailings sand, crushed stone, water and admixtures in the multi-component composite industrial solid waste concrete are 280, 60, 90, 400, 280, 1100, 170 and 7.5 respectively, in grams, and their proportions to the total weight of concrete are 11.7%, 2.5%, 3.8%, 16.8%, 11.7%, 46.1%, 7.1% and 0.3% respectively.
[0068] Cement: Use silicate cement P.O42.5;
[0069] Fly ash: primary fly ash, loss on ignition 4.5%, D50 particle size 6.017μm, fly ash particles smaller than 3μm content 25%, fly ash particles 3μm-32μm content 71%.
[0070] Slag: S95 grade, mass fraction 1.46, activity coefficient 0.31, alkalinity coefficient 0.91, 28-day activity coefficient 96%, fluidity ratio 95.5%, loss on ignition 2.7%, glass content 88%.
[0071] Fine aggregate: tailings sand 41.2%, machine-made sand 58.8%, fineness modulus 2.6. Apparent density of machine-made sand 2650kg / m 3 , bulk density 1850kg / m 3 , crushing value 25%; tailings sand apparent density 2650kg / m 3 , bulk density 1630kg / m 3 .
[0072] Coarse aggregate: crushed stone with particle size of 5-20mm and 5-31.5mm in continuous grading.
[0073] Admixture: Polycarboxylic acid high-efficiency water reducing agent, water reducing rate 25%.
[0074] Preparation method of multi-component composite industrial solid waste concrete:
[0075] Determine the strength grade as: 30MPa≤strength grade<50MPa; pretreat fly ash, slag, machine-made sand and tailings sand; weigh and measure the pretreated fly ash, slag, machine-made sand and tailings sand with cement, water, admixtures and gravel; add the measured fly ash, slag, machine-made sand, tailings sand, cement and gravel into a mixer and dry mix for 10 minutes; add half of the measured water and admixture into the mixer and stir for 10 minutes; add the remaining water and admixture and mechanically stir until uniform.
[0076] According to the experimental steps in Example 1, the compressive strength of the concrete sample in this example after 60 days of curing is 46 MPa.
[0077] Example 3
[0078] The weights of cement, fly ash, slag, machine-made sand, tailings sand, crushed stone, water and admixtures in multi-component composite industrial solid waste concrete are 340, 40, 100, 430, 210, 1120, 160 and 9.6 respectively, in grams, and their proportions to the total weight of concrete are 14.1%, 1.7%, 4.2%, 17.8%, 8.7%, 46.5%, 6.6% and 0.4% respectively.
[0079] Cement: Use silicate cement P.O52.5;
[0080] Fly ash: primary fly ash, loss on ignition 4%, D50 particle size 6.017μm, fly ash particle content less than 3μm 29%, fly ash particle content of 3μm-32μm 70%.
[0081] Slag: S95 grade, mass fraction 1.46, activity coefficient 0.31, alkalinity coefficient 0.91, 28-day activity coefficient 97%, fluidity ratio 97%, loss on ignition 2.1%, glass content 89%.
[0082] Fine aggregate: tailings sand 32.8%, machine-made sand 67.2%, fineness modulus 2.6. Apparent density of machine-made sand 2700kg / m 3 , bulk density 1845kg / m 3 , crushing value 25%; tailings sand apparent density 2671kg / m 3 , bulk density 1598kg / m 3 .
[0083] Coarse aggregate: crushed stone with particle size of 5-20mm and 5-31.5mm in continuous grading.
[0084] Admixture: Polycarboxylic acid high-efficiency water reducing agent, water reducing rate 28%.
[0085] Preparation method of multi-component composite industrial solid waste concrete:
[0086] Determine the strength grade as: 50MPa≤strength grade<100MPa; pretreat fly ash, slag, machine-made sand and tailings sand; weigh and measure the pretreated fly ash, slag, machine-made sand and tailings sand with cement, water, admixtures and gravel; add the measured fly ash, slag, machine-made sand, tailings sand, cement and gravel into a mixer and dry mix for 8 minutes; add half of the measured water and admixture into the mixer and stir for 8 minutes; add the remaining water and admixture and mechanically stir until uniform.
[0087] According to the experimental steps in Example 1, the compressive strength of the concrete sample after 60 days of curing in this example is 50.9 MPa.
[0088] Example 4
[0089] The weights of cement, fly ash, slag, limestone powder, silica fume, natural sand, machine-made sand, tailings sand, crushed stone, water and admixtures in multi-component composite industrial solid waste concrete are 412.8, 63.5, 63.5, 31.75, 63.5, 70.4, 422.4, 211.2, 1108, 158 and 11.34 respectively, in grams, and their proportions to the total weight of concrete are 15.8%, 2.4%, 2.4%, 1.2%, 2.4%, 2.7%, 16.1%, 8.1%, 42.3%, 6.0% and 0.4% respectively.
[0090] Cement: Use silicate cement P.O52.5;
[0091] Fly ash: primary fly ash, loss on ignition 4.3%, D50 particle size 6.017μm, fly ash particles smaller than 3μm content 30%, fly ash particles 3μm-32μm content 66%.
[0092] Slag: S95 grade, mass fraction 1.46, activity coefficient 0.31, alkalinity coefficient 0.91, 28-day activity coefficient 97.5%, fluidity ratio 97.2%, loss on ignition 2.7%, glass content 88%.
[0093] Limestone powder: D50 particle size is 2.859μm, the content of limestone powder particles smaller than 3μm is 52%, and the content of limestone powder particles between 3μm and 32μm is 48%.
[0094] Silica fume: SiO2 content 97%, loss on ignition 2.4%, activity index 107%.
[0095] Fine aggregate: tailings sand 33.3%, machine-made sand 66.7%, fineness modulus 2.6. Apparent density of machine-made sand 2700kg / m 3 , bulk density 1845kg / m 3 , crushing value 25%; tailings sand apparent density 2671kg / m 3 , bulk density 1598kg / m 3 .
[0096] Coarse aggregate: crushed stone with particle size of 5-20mm and 5-31.5mm in continuous grading.
[0097] Admixture: Polycarboxylic acid high-efficiency water reducing agent, water reducing rate 28%.
[0098] Preparation method of multi-component composite industrial solid waste concrete:
[0099] Determine the strength grade as: 50MPa≤strength grade<100MPa; pretreat fly ash, slag, machine-made sand and tailings sand; weigh and measure the pretreated fly ash, slag, machine-made sand and tailings sand with cement, water, admixtures and gravel; add the measured fly ash, slag, machine-made sand, tailings sand, cement and gravel into a mixer and dry mix for 10 minutes; add half of the measured water and admixture into the mixer and stir for 10 minutes; add the remaining water and admixture and mechanically stir until uniform.
[0100] According to the experimental steps in Example 1, the compressive strength of the concrete sample in this example after 60 days of curing was 80.3 MPa.
[0101] The distribution ratios of the concrete groups in the other embodiments are shown in the following table:
[0102] Table 1 Concrete mix ratio
[0103]
[0104]
[0105]
[0106]
[0107] The compressive strengths of the other embodiments tested according to the experimental method of embodiment 1 are as follows:
[0108] Table 2 Measured compressive strength of concrete
[0109]
[0110]
[0111] The proportions of the multi-component composite industrial solid waste concrete that do not meet the design of the present invention are all comparative examples.
[0112] In addition to the above embodiments, the present invention may also have other implementation modes. Any technical solutions formed by equivalent replacement or equivalent transformation shall fall within the protection scope required by the present invention.
Claims
1. A multi-component composite industrial solid waste concrete, characterized by: It includes several strength grades, which are 20MPa≤strength grade<30MPa, 30MPa≤strength grade<50MPa and 50MPa≤strength grade<100MPa. The concrete composition ratios of the corresponding strength grades are as follows: 20MPa≤Strength grade<30MPa: cement 5.8%-11.5%, fly ash 2.0%-8.0%, slag 1.5%-8.0%, limestone powder 0%-10.0%, machine-made sand 18.0%-25.0%, tailings sand 10.0%-23.0%, water 7.0%-8.5%, admixture 0.29%-0.42%; 30MPa≤Strength grade<50MPa: cement 7.0%-17.0%, fly ash 2.0%-7.0%, slag 1.5%-7.0%, limestone powder 0%-10.0%, machine-made sand 9.5%-20.0%, tailings sand 8.5%-22.5%, water 6.5%-7.5%, admixture 0.27%-0.36%; 50MPa≤Strength grade<100MPa: cement 8.0%-18.0%, fly ash 1.5%-6.0%, slag 1.5%-6.0%, limestone powder 0%-8.0%, silica fume 0%-2.5%, natural sand 0%-32.5%, machine-made sand 16.0%-22.5%, tailings sand 7.5-9.5%, water 5.0-7.0%, admixture 0.4-0.5%; Among them, the proportion of each component is the proportion of the total weight of concrete, and the remaining components are crushed stone or natural sand.
2. The multi-component composite industrial solid waste concrete according to claim 1, characterized in that: The cement is silicate cement P.O42.5 when the concrete strength grade is between 20MPa and 50MPa, and is silicate cement P.O52.5 when the concrete strength grade is between 50MPa and 100MPa.
3. The multi-component composite industrial solid waste concrete according to claim 1, characterized in that: The fly ash is first-class fly ash, with a loss on ignition of ≤5% and a D50 particle size of 6.017 μm, wherein the content of fly ash particles smaller than 3 μm is ≤30% and the content of fly ash particles of 3 μm-32 μm is ≥66%.
4. The multi-component composite industrial solid waste concrete according to claim 1, characterized in that: The slag is of S95 grade, with a mass fraction of 1.46, an activity coefficient of 0.31, an alkalinity coefficient of 0.91, a 28-day activity coefficient of ≥95%, a fluidity ratio of ≥95%, a loss on ignition of ≤3.0%, and a glass content of ≥85%.
5. The multi-component composite industrial solid waste concrete according to claim 1, characterized in that: The D50 particle size of the limestone powder is 2.859 μm, wherein the content of limestone powder particles smaller than 3 μm is 52%, and the content of limestone powder particles of 3 μm-32 μm is 48%.
6. The multi-component composite industrial solid waste concrete according to claim 1, characterized in that: The SiO2 content of the silica fume is ≥96%, the ignition loss is ≤2.5%, and the activity index is ≥105%.
7. The multi-component composite industrial solid waste concrete according to claim 1, characterized in that: The tailings sand and machine-made sand are mixed into fine aggregate in a ratio of 25%-45% of tailings sand and 55%-75% of machine-made sand, and the fineness modulus of the fine aggregate is 2.
6.
8. The multi-component composite industrial solid waste concrete according to claim 7, characterized in that: The apparent density of the machine-made sand is 2600-2800 kg / m 3 , bulk density 1750-1900kg / m 3 , crushing value 25%; tailings sand apparent density 2600-2800kg / m 3 , bulk density 1500-1700kg / m 3 .
9. The multi-component composite industrial solid waste concrete according to claim 1, characterized in that: The admixture is a polycarboxylic acid high-efficiency water reducing agent, and the water reducing rate is ≥25%.
10. A method for preparing multi-component composite industrial solid waste concrete applicable to any one of claims 1 to 9, characterized in that: The following steps are included: S1. Determine the strength grade of concrete according to usage requirements; S2. Pre-treat fly ash, slag, limestone powder, machine-made sand and tailings sand; S3, according to the concrete strength grade determined in step 1, weigh and measure the pre-treated fly ash, slag, limestone powder, machine-made sand and tailings sand with cement, water, admixtures, silica fume, natural sand and crushed stone; S4, adding the fly ash, slag, limestone powder, machine-made sand, tailings sand, cement, silica fume, natural sand and gravel measured in step 3 into a mixer, and dry mixing for 5-10 minutes; S5. Add half of the water and admixture measured in step 3 into the mixer and stir for 5-10 minutes until the concrete is loose. S6. Add the remaining water and admixtures, stir mechanically until uniform, and carry out standard curing after casting.
Citation Information
Cited By
Design method of goaf grouting material, grouting material and grouting method
CN121545642A
A design method of a goaf grouting material, a grouting material and a grouting method
CN121545642B